Smart Tracking of Human Location and Events Based on WPS using Android Technology - P. Padmavathy; C. Balakrishnan (International Journal of Computer Sciences and Engineering, 2014)
Predicting the human location-based on the current tracking system is inefficient and costly due to data transmission where the cost is based on the usage of data. The aim is to develop an efficient child awareness system which is essential software that uses the asset tracking algorithm to predict the exact location of the child. This tracking system allows the parents to monitor their childï¿½s mobile phone to trace the location and the mobile events thereby developing an efficient asset tracking solution to preserve valuable mobile assets by means of location and context awareness route learning techniques. All call events and text content can be seen by the parents and location can be traced (through the utilization of GPS and WPS). This system uses android based smart phones for triggering the software that sends alert to the parent when the child moves out of the geographical zone. The centralized server is used to store all notification and updated information of the child. This paper provides tracking approach to create awareness to the parents about their childï¿½s behaviour.